(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The main objective of the article is the consideration of features of treatment by the Kazakh translators, poets and writers of the Pushkin’s novel about Eugene Onegin and Tatyana Larina. The author of the article proves that ‘Eugene Onegin» owing to the polysemy and inexhaustibility of the contents leads «the second life» in other languages, considers features of «reading» of Pushkin’s novel by Abay, Aset Naymanbayev and other akyns of the 19th century. Abay on the basis of the plot of «Eugene Onegin» created a new genre of the epistolary novel in the Kazakh literature, and Aset Naymanbayev, Kuat Teribayev and Sapargali Alimbetov interpreted the Pushkin’s plot in the genre of the romantic poem – dastan. The article also analyses the peculiarities of use of Pushkin’s traditions by Azilkhan Nurshaikhov at creating the plot of the novel «Makhabbat, Kyzyk Mol Zhyldar», it considers Pushkin’s influence on the treatment of the actions of the main character of this novel and the last poem of the writer about love, it defines common ground in plots of both writers. The author of article proves that Azilkhan Nurshaikhov who was looking for a new genre form for the plots addressed to Pushkin’s experience as the first experimenter of the novelistic genre in the Russian literature.